The effects of audio-visual perceptual characteristics on environmental health of pedestrian streets with traffic noise: A case study in Dalian, China - Ren, Xinxin; Wei, Peng; Wang, Qiran; Sun, Wei; Yuan, Minmin; Shao, Shegang; Zhu, Dandan; Xue, Yishan (Frontiers in Psychology, 2023)
The COVID-19 pandemic has affected city dwellers’ physical and mental health and has raised concerns about the health of urban public spaces. This field investigation research in Dalian, China, examined the perceived audio-visual environment characteristics of urban pedestrian streets with traffic noise and their influences on the environmental health of the pedestrian streets. Five indicators reflecting psychological responses to environmental characteristics (willingness to walk, relaxation, safety, beauty, and comprehensive comfort) were used to measure environmental health of pedestrian streets with traffic noise. The results showed that safety was rated the highest, and willingness to walk was evaluated as the lowest among health evaluation indicators. The imageability and openness of the streetscape were associated with each health evaluation indicator. In contrast, the rhythm and continuity of the street buildings had a greater effect on willingness to walk than the other health indicators. There were negative correlations between LAeq for traffic noise and health evaluations. Positive health evaluations were observed when LAeq was less than 55 dBA. In contrast, soundscape indicators showed positive correlations with health evaluations, and acoustic comfort and noise annoyance, rather than sound preference and subjective loudness were associated with each health evaluation indicator. In terms of the combined audio-visual factors, acoustic comfort, the quantity of greening, annoyance, sky visibility, spatial scale, and building distance were examined as the determining factors affecting health evaluations, and 55.40% of the variance in health evaluations was explained by the soundscape and streetscape indicators. The findings provide references for better understanding the relationships between healthy experience and audio-visual perceptions. Moreover, they enable environmental health quality optimisation of pedestrian spaces considering audio-visual indicators and approaches in the post-epidemic era.